Revitalisasi Objek Wisata Taman Kyai Langgeng Kota Magelang Pasca Pandemi COVID-19 - Agni, Agasi; Sujatmiko; Yuni Kurniasih (Jurusan Administrasi Publik, FISIP, Universitas Sriwijaya, 2023)
This qualitative research aims to analyze the revitalization of the Kyai Langgeng Park (Taman Kyai Langgeng or TKL), a city tourism destination in Magelang City after the COVID-19. The research location was carried out at the Magelang City which was affected by the COVID-19. The results of data analysis using an interactive model show that the revitalization carried out by the management of TKL includes physical intervention, economic, social and institutional rehabilitation. In carrying out the revitalization of TKL, managers are constrained by limited human resources and budget. Revitalization efforts continue to be carried out by the management of TKL in order to increase the number of tourists and regional original income of Magelang City in accordance with the company's vision and mission.